COVID-19, School Closures, and Student Learning Outcomes: New Global Evidence from PISA - Maciej Jakubowski; Tomasz Gajderowicz; Harry Patrinos (Global Labor Organization (GLO), 2024)
The COVID-19 pandemic resulted in significant disruption in schooling worldwide. This paper uses global test score data to estimate learning losses. It models the effect of school closures on achievement by predicting the deviation of the most recent results from a linear trend using data from all rounds of the Programme for International Student Assessment. Scores declined by an average of 14 percent of a standard deviation, roughly equal to seven months of learning. Losses were greater for students in schools that faced relatively longer closures, boys, immigrants, and disadvantaged students. Educational losses may translate into significant national income losses over time.
Keywords: I19; I20; 330; COVID-19; learning loss; student achievement; PISA; international large-scale assessments